Place des gymnospermes endémiques des Andes méridionales dans la végétation du ChiIi - Woltz, Philippe (Lazaroa, 1985)
This paper deals mainly with the gymnosperms in their natural environment. Most of the 10 species are highly endemic taxa of the genera Araucaria, Saxegothaea, Podocarpus, Dacrydium, Autrocedrus, Fitzroya and Pilgerodendron representing 5 families. Their geographical distribution is not yet well known.